Annual mowing has the potential to reduce the invasion of herbaceous Lupinus polyphyllus - Ramula Satu (SPRINGER, 2025)
In order to manage invasive plant species efficiently, it is necessary to have a thorough understanding of different strategies of population control, including the underlying mechanisms of action and the consequences for target populations. Here, I explored the effectiveness of biomass removal as a method of control for the invasive perennial herbLupinus polyphyllus. More specifically, using seed material from 11 populations, I assessed among-population variation (if any) in plant compensatory growth as a response to annual biomass removal under standardised growing conditions over two consecutive years, and quantified the demographic effects of a single biomass-removal event. In all study populations, annual biomass removal reduced plant size, flowering probability, and shoot and root biomass. Biomass removal also reduced plant survival and the number of flowering shoots, but these effects were pronounced at certain time points only. A population-level demographic analysis revealed that a single biomass-removal event considerably decreased the long-term population growth rate (lambda); this decline in lambda was due to a reduction in plant fecundity followed by survival and growth. These findings suggest that annual mowing has the potential to curb invasions ofL. polyphyllusbecause plants are not able to fully compensate for drastic biomass loss.